Effects of supplementing methionine and lysine in a lactation diet containing high concentrations of corn by-products - C.R. Mullins; D. Weber; E. Block; John F. Smith (Kansas Agricultural Experiment Station Research Reports, 2011)
Ninety-six lactating Holstein cows were used to determine the effects of using commercial supplements to supply additional lysine and methionine in diets containing large proportions of corn by-products. Cows were assigned to 1 of 8 pens. Pens were offered rations formulated to differ in metabolizable lysine and methionine supply. The study was divided into 2 periods. During period 1, cows received similar diets, but the treatment diet supplied supplemental lysine and methionine. During period 2, the treatment diet was modified to reduce dietary crude protein. Feed intake and production were monitored daily, and milk components were analyzed 3 days per week for 4 weeks. Diet did not alter feed intake or milk production. During period 2, dietary crude protein and milk urea nitrogen (MUN) were decreased without sacrificing performance.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Dairy; By-product; Lysine; Methionine; Milk yield